DIGITAL MARKETING STRATEGI OF WATCH BRAND CASE MYLUXGOODS.ID (The Indonesian Journal of Business Administration, 2021)
The shopping behavior from offline to online which has become a phenomenon in Indonesia is an opportunity for online businesses. Myluxgoods.id is an online store that was formed in September 2019 that sells watch products that focus on selling online because the system used is dropship. At this stage, myluxgoods.id focuses on increasing sales and branding so that myluxgoods.id products can be recognized by the target market segments. Therefore, by selling online myluxgoods.id requires the right digital marketing strategy so that the business plan can be realized. Quantitative methods are used to obtain and collect information needed to achieve the targets of the plans that have been made, SWOT analysis, IPA analysis is used to see the performance of myluxgoods.id, to identify business situations used internal analysis and external analysis, internal analysis used. power and value chain analysis, as well as external analysis used, namely strength analysis and analysis of competitors. Based on the results of the analysis, myluxgoods.id has to do several digital marketing points, including improving in terms of content, trying SEO (Search Engine Optimization) methods, influencer endorsements, and scale up promotions.Key words: Market wants and needs, company performance, digital marketing.